Emergency department resource utilization during Ramadan: distinct and reproducible patterns over a 4-year period in Abu Dhabi. (February 2018) - Balhara, Kamna S.; Levin, Scott; Cole, Gai; Scheulen, James; Anton, Xavier P.; Rahiman, Hameed Ali Fazlur; Stewart de Ramirez, Sarah A.
Abstract : Objectives: Emergency Department (ED) patient arrivals vary daily and change considerably during holidays, posing challenges to resource allocation. Ramadan, during which observant Muslims follow a daily fasting period for ∼30 days, could represent a unique annual circumstance that predictably alters ED arrivals in predominantly Muslim populations. Our study examined an adult and pediatric ED in the United Arab Emirates to determine whether arrival patterns and patient characteristics differed during Ramadan. Methods: Hourly arrivals, census (number of patients in ED at any given time), and visit characteristics were retrospectively compared for Ramadan versus non-Ramadan periods over 4 years (2010–2013). Hourly arrivals and census were plotted using two-way repeated-measures analysis of variance. Differences in characteristics were examined using the χ 2 -test and Wilcoxon rank sum tests. Results: Ramadan adult and pediatric ED arrival patterns differed significantly ( P <0.001) from non-Ramadan days, with sharp decreases after the fast was broken around 6 p.m. (sunset), followed by steep increases by 8:30 pm. The median daily adult arrivals were similar [143 (Ramadan) vs. 148 (non-Ramadan); P =0.060], with slightly decreased length-of-stay (7%; P <0.001) during Ramadan. The median daily pediatric arrivals were lower during Ramadan (43 vs. 57; P <0.001), with decreased length-of-stay (20%; P <0.001). Arrival pattern shifts led to significant census redistribution to evening hours. Patient characteristics were similar during both periods. Conclusion: A distinct, predictable pattern of arrivals emerged during Ramadan. EDs serving predominantly Muslim populations or anticipating increases in Muslim patients in their catchment region may benefit from advanced planning for efficient distribution of provider hours during Ramadan.